Overview of the Job-related Affective Well-being Scale (JAWS) - Novak, Tihana (Array, 2007)
The paper is about application of JAWS (Job Affected Well-being Scale) that has been designed by Katawick, Fox, Spector, Kelloway (2000) for measuring the different affects that have an affect people’ s perceptions on their subjective job-related well-being. Each item is an emotion, negative or positive and respondents are asked how often they have experienced each at work over the prior 30 days. Responses are made with five-point scale with anchors: never, rarely, sometimes, quite often, extremely often and always. Croatian version of JAWS will be tested on University staff – as a pilot study for the scientific project “ Emocionalno dobrostanje i sagorijevanje na poslu zatvorskog osoblja” . This paper will present the findings of the reliability analyses of the Croatian version of the scale.